An investigation of the effect of anecdotal information on the choice of a healthcare facility. (July 2018) - Chalil Madathil, Kapil; Greenstein, Joel S.
Abstract: This article includes two studies investigating the impact of anecdotal healthcare information from the Internet on healthcare decisions. The availability of anecdotal information on the Internet through social media and peer support groups has increased the risk of the dissemination of misleading information. The first study investigated the effect of demographics, quality of life, health status and public reports usage on the use of anecdotal healthcare information from the Internet. The second employed a 2 (anecdotal information presented as videos supporting and contradicting public report information) * 2 (phase of introduction of anecdotal information: early, late) between-subjects experimental design to investigate the consumer's choice between two health facilities, the level of confidence in the decision, the knowledge acquired and the workload experienced. The results from the first study found that age, gender, educational level, health status and public report usage were significant predictors of consumer use of anecdotal information on the Internet. The results from the second suggest that the probability of making the optimal choice was reduced by more than half when contradicting rather than supporting anecdotal information was presented first. The data from anecdotal information became the anchor points for developing an understanding of the healthcare situation, meaning initial perceptions did not change after the presentation of the more reliable public reports. Because of comprehension issues related to public reports, consumers may give more weight to anecdotal information found online. Thus, new approaches are needed to ensure the former is engaging for a wide range of healthcare consumers. Highlights: Anecdotal information about health systems is available to the public. This can impact the utility of public reports generated by Federal entities. Public report information seekers are very likely to look at anecdotal information. Contradictory anecdotal information presented first impacted the final choice. New approaches are required to ensure the public report usage by consumers.